Community Empowerment Through Increasing Productive Land Use for Sustainable Food Houses - Ratih Damayanti, Gusti Ayu; Ulum, Hafizatul; Rifai, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Rumah Pangan Lestari program is a program to utilize limited land potential, especially yards. This program aims to ensure the maximum nutritional value of the food consumed by the family and make the best use of limited yard land, so as to minimize expenses and become a source of income for the local community. Therefore, we implement and run this sustainable food house program, which provides socialization and training, field visits, and food crop nurseries for the Gelasar village community. This activity took place during the implementation of the 38th KKN T period 2024. Administrator,https://upland.psp.pertanian.go.id/artikel/1703313612/rumah-pangan-lestari-rpl-solusi-bagi-masyarakat, 14122023 Dinas Ketahanan Pangan Provinsi Nusa Tenggara Barat, https://diskapang.ntbprov.go.id/pages/kawasan-rumah-pangan-lestari-krpl.Annisahaq, H., Nuhfil, H., Syafrial. (2014). Pengaruh Program Kawasan Rumah Lestari (KRPL) dalam Mendukung Kemandirian Pangan dan Kesejahteraan Rumah Tangga.Habitat. Vol 25 (1). 32-39 pp.Arafat, Y. (2018, September). Studi Penerapan Pendidikan Karakter Di Sekolah Tinggi Keguruan Dan Ilmu Pendidikan (STKIP) Bima. In Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala (pp. 453-460).Ashari, Saptana, Tri, B. P. (2012). Potensi dan Prospek Pemanfaatan Lahan Pekarangan untuk Mendukung Ketahanan Pangan. Forum Penelitian Agro Ekonomi. Vol 30 (1). 13-30 pp.Cristianingrum, Gigih, I. P. (2020). Penerapan Sistem Kawasan Rumah Pangan Lestari (KRPL) di Desa Baru, Kecamatan Manggar, Kabupaten Belitung Timur. Ikraith- Abdimas. Vol. 3. No. 1. 89-94.Dirawan, G. D., & Muhdar, M. (2022). STRATEGI PEMANFAATAN JASA LINGKUNGAN PADA HUTAN KEMASYARAKATAN DI KABUPATEN DOMPU. Humano: Jurnal Penelitian, 13(2), 65-73.Faqih, A. 2015. Persepsi Anggota Kelompok Tani terhadap Peranan Kelompok Tani; Logika: Jurnal Ilmiah LEMLIT Unswagati Cirebon. Vol 15 (3). 72-89 pp.Mardiharini, M. 2011. Model Kawasan Rumah Pangan Lestari dan Pengembangannya ke Seluruh Provinsi di Indonesia. Warta Penelitian dan Pengembangan Pertanian. Vol 33 (6). 3-5 pp.Purwantini, T. B., Saptan, Sri, S. S. 2012. Program Kawasan Rumah Pangan Lestari (KRPL)di Kabupaten Pacitan: Analisis Dampak dan Antisipasi ke Depan. Analisis KebijakanPertanian. Vol 10 (3). 239-256 pp.Undang-Undang Nomor 18 Tahun 2012 Tentang Pangan